An in vitro comparative evaluation of different intraorifice barriers on the fracture resistance of endodontically treated roots obturated with gutta-percha - Gupta, Abhishek (J Conserv Dent, 2016)
AIM: To compare and evaluate the root reinforcement potential of four different intraorifice barriers: Mineral trioxide aggregate (MTA), resin-modified glass ionomer cement (RMGIC), fiber-reinforced composite (FRC), and nanohybrid composite (NC). MATERIALS AND METHODS: Seventy-five mandibular premolars were decoronated to a standardized length, and prepared and obturated with gutta-percha and AH Plus sealer. Except for control specimens, the coronal 3-mm gutta-percha was removed and filled with different materials. The specimens (75) were divided into five groups (n = 15) on the basis of the intraorifice barrier material used. Group 1: MTA, Group 2: RMGIC, Group 3: FRC, Group 4: NC, Group 5: no barrier (control). Fracture resistance of the specimens was tested. RESULTS: Fracture resistance of roots was significantly affected by the type of intraorifice barrier used and the following pattern was observed: RMGIC > FRC > NC > MTA. CONCLUSION: Intraorifice barriers can be regarded as a viable choice to reduce the occurrence of postendodontic root fractures. Among the four tested materials, RMGIC showed the maximum reinforcement.